Effort at Implementing ICT Policy in Basic Schools in Ghana: An Assessment of Available Facilities and Resources for Successful ICT Education within the Atwima Nwabiagya District in Ashanti Region - Opoku, Maxwell Peprah; Badu, Eric; Alupo, Beatrice Atim (ASPENSI in Bandung, Indonesia, 2016)
ABSTRACT: ICT (Information and Communication Technology) has potential to make educational resources accessible entirely. Therefore, knowledge is not limited to a geographical area and instrumental in offering options for information sharing, archiving, and retrieving. Thus, governments have to prioritize ICT education by supporting schools with materials for teaching and learning. The study aimed to document resources and materials available for teaching and learning of ICT in Atwima Nwabiagya District in Ghana. The study adopted case study design and a mixed method of data collection. In all, a total of 512 were recruited to be part of the study. The study found that the government of Ghana has failed to support schools with the needed resources for teaching and learning of ICT. Schools lack ICT labs, internet connection, and other resources needed to make teaching a success. The current resources available in schools will not make it possible for the country to achieve its objective with making ICT education possible for all children in basic schools in Ghana. Therefore, it is high time the government put in much resource in effort to make this policy a reality.Â KEY WORD: Information and Communication Technology; Education; Students and Teachers; Resources Support; Implementation of Policy.Â RESUME: âUpaya Pengimplementasian Kebijakan TIK (Teknologi Informasi dan Komunikasi) di Sekolah-sekolah Dasar di Ghana: Sebuah Penilaian terhadap Ketersediaan Fasilitas dan Sumber Daya untuk Keberhasilan Pendidikan TIK di Kabupaten Atwima Nwabiagya di Daerah Ashantiâ. TIK memiliki potensi untuk membuat sumber daya pendidikan dapat diakses sepenuhnya. Karena itu, pengetahuan tidak terbatas pada wilayah geografis dan secara instrumental menawarkan pilihan untuk berbagi, mengarsipkan, dan mengunduh informasi. Jadi, pemerintah harus memprioritaskan pendidikan TIK dengan mendukung sekolah menyediakan bahan-bahan untuk mengajar dan belajar. Penelitian ini bertujuan untuk mendokumentasikan sumber daya dan bahan yang tersedia untuk mengajar dan belajar TIK di Kabupaten Atwima Nwabiagya di Ghana. Studi ini mengadopsi desain studi kasus dan metode campuran dalam pengumpulan data. Semuanya, sebanyak 512 orang direkrut untuk menjadi bagian dari penelitian ini. Studi menunjukan bahwa pemerintah Ghana gagal dalam mendukung sekolah dengan sumber daya yang dibutuhkan untuk mengajar dan belajar TIK. Sekolah kekurangan laboratorium TIK, koneksi internet, dan sumber daya lainnya yang dibutuhkan untuk membuat pengajaran sukses. Ketersediaan sumber daya saat ini di sekolah tidak memungkinkan bagi negara mencapai tujuannya untuk menjadikan pendidikan TIK memungkinkan bagi semua anak di sekolah-sekolah dasar di Ghana. Karena itu, sudah saatnya pemerintah memasukan banyak sumber daya dalam upaya menjadikan kebijakan ini menjadi kenyataan.KATA KUNCI: Teknologi Informasi dan Komunikasi; Pendidikan; Murid dan Guru; Sumber Dukungan; Implementasi Kebijakan.Â Â Â Â About the Authors: Maxwell Peprah Opoku and Eric Badu are the Lecturers at the Centre for Disability Rehabilitation Studies KNUST (Kwame Nkrumah University of Science and Technology), Kumasi, Ghana. Beatrice Atim Alupo is a Lecturer at the Institute of Governance, Humanities, and Social Sciences PAU (Pan African University), Soa-Yaounde, Cameroon. Corresponding author is: abizep4@yahoo.com How to cite this article? Opoku, Maxwell Peprah, Eric Badu & Beatrice Atim Alupo. (2016). âEffort at Implementing ICT Policy in Basic Schools in Ghana: An Assessment of Available Facilities and Resources for Successful ICT Education within the Atwima Nwabiagya District in Ashanti Regionâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.9(1) May, pp.183-194. Bandung, Indonesia: Minda Masagi Press and UPI Bandung, ISSN 1979-0112.Chronicle of the article: Accepted (December 1, 2015); Revised (February 15, 2016); and Published (May 20, 2016).